Comparação entre os efeitos da posição prona e do óxido nítrico inalatório sobre oxigenação, mecânica respiratória, lesão histopatológica e inflamação na lesão pulmonar aguda induzida experimentalmente - Satrapa, Débora Avellaneda Penatti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Background/Objectives: The Acute Respiratory Distress Syndrome (ARDS) is associated with high mortality rate despite better understanding of its pathophysiology and treatment advances. There are several adjuvant therapies that can be associated to mechanical ventilation (MV), among which stands out the prone position, which allows homogeneous tidal volume (VT) distribution and promotes alveolar recruitment; and inhaled nitric oxide (iNO) which promotes selective pulmonary vasodilation directing blood flow from areas poorly ventilated to well-ventilated areas and decreased perfusion, optimizing the ventilation/perfusion ratio and improving oxygenation with reduced pulmonary vascular resistance. Improved ventilation/perfusion ratio, allows the use of lesser aggressive mechanical ventilation (MV) treatment, which reduces the risk of lung injury induced by MV and morbidity. Objective: To compare the effects of prone position with iNO on oxygenation, respiratory mechanics, inflammatory and histological injury in an experimental model of acute lung injury (ALI). Methods: Fifty rabbits were instrumented with tracheotomy and vascular access and mechanically ventilated. ALI was induced by tracheal infusion of warm saline (30mL/kg, 38°C). Rabbits underwent protective conventional mechanical ventilation (CMV) were divided in four groups: 1) Animals with ALI in protective CMV + supine position (GVMS, n=15), 2) animals with ALI in protective CMV + prone position (GVMP, n=15) and 3) animals with ALI in protective CMV + iNO in supine position (GVNO, n=15). Additionally, there were five animals without lung injury submitted to protective CMV (Healthy group - GS, n=5). The outcomes were oxygenation, measured by PaO2/FiO2 ratio and oxygenation index (OI), lung inflammation assessed by the percentage of polymorphonuclear cells (PMN) in bronchoalveolar lavage (BAL) and TNF-alpha measured in BAL, and histological pulmonary injury determined by a injury ...

Fundamentação/Objetivos: A Síndrome do Desconforto Respiratório Agudo (SDRA) cursa com altos índices de mortalidade apesar do melhor entendimento de sua fisiopatologia e avanços no tratamento. Existem várias terapias adjuvantes à ventilação mecânica (VM), dentre as quais se destaca a posição prona, que possibilita homogeneização da distribuição do volume corrente (VC) e promove recrutamento alveolar, e o óxido nítrico inalatório (NOi) que promove vasodilatação pulmonar seletiva direcionando o fluxo sanguíneo de áreas mal ventiladas para áreas bem ventiladas e com perfusão diminuída, otimizando a relação ventilação/perfusão e melhorando a oxigenação, com diminuição da resistência vascular pulmonar. Pela melhora da relação ventilação/perfusão, o gás pode permitir o emprego de VM menos agressiva, que, por sua vez, pode diminuir o risco de lesão pulmonar induzida pela VM e a morbidade. Objetivo: comparar os efeitos da posição prona com os do NOi sobre a oxigenação, mecânica respiratória, lesão histopatológica e inflamatória em modelo experimental de lesão pulmonar aguda (LPA). Métodos: Cinquenta coelhos foram instrumentados com traqueostomia e acessos vasculares e ventilados mecanicamente. A LPA foi induzida por infusão traqueal de salina aquecida (30mL/Kg, 38°C). Os coelhos foram submetidos à VMC protetora e distribuídos em quatro grupos: 1) animais com LPA em VMC protetora em posição supina (GVMS; n=15); 2) animais com LPA em VMC protetora + posição prona (GVMP; n=15); 3) animais com LPA em VMC protetora + NOi em posição supina (GVNO; n=15) e 4) animais sem lesão pulmonar submetidos à VMC protetora (sadio – GS; n=5). Os desfechos foram: oxigenação, avaliada pela relação PaO2/FiO2 e índice de oxigenação (IO); inflamação pulmonar, avaliada pela porcentagem de polimorfonucleares (PMN) no lavado broncoalveolar (BAL) e pelo nível de TNF-alfa medido no BAL e lesão ...
Keywords: Decúbito ventral; Respiracao artificial; Oxido nitrico; Sindrome do desconforto respiratorio - Fisiopatologia; Pulmões - Doenças; Respiratory Distress Syndrome; Prone Position